Sexual function and sexual activity in young total hip arthroplasty Chinese patients: A retrospective cohort study - Yang, Daishui; Zhang, Jie; Zhang, Kexin; Zhou, Yanlin; Peng, Xiao; Wang, Ling; Liu, Tang (Frontiers in Surgery, 2023)
Introduction As an essential component of quality of life, there is limited evidence of sexual function (SF), especially for young patients, before and after total hip arthroplasty (THA). This study aims to enhance the understanding of SF status and assess patient perspectives before and after THA. Methods A total of 109 patients who received THA were enrolled into our retrospective cohort study. To assess the SF status before and after THA, patients were required to fill out a standardized SF questionnaire [female sexual function index (FSFI) or brief sexual function inventory (BSFI) for males] and a specifically designated questionnaire regarding perspectives toward sexual activity and attitudes to sexual-related information. Results Total average scores of both FSFI and BSFI were higher post-THA. For female patients, the FSFI scores were significantly higher in the domain of desire, orgasm, and satisfaction (p < 0.05). For male patients, the BSFI scores were also improved in the sex drive and satisfaction domain post-operation (p < 0.05). A large proportion of the patients (64.22%) reported difficulty in sexual activity preoperatively, primarily due to restricted motion (82.86%) and hip pain (74.29%). After a successful procedure, there was a reduction in difficulty in patients’ sexual activity post-THA (39.45%), mainly attributed to less pain (72.09%) and greater mobility (79.07%). In addition, subgroup analysis results indicated that gender and severity of hip stiffness and pain were crucial factors that could affect the patient's SF status. Furthermore, the majority of patients reported that they desired information concerning sexual activity, but only 12.84% of patients were informed well. Patients’ preferred channels to acquire sexual-related information was a booklet (65.59%, n = 61), followed by informing a surgeon and a nurse. The most concerning questions regarding the sexual activity of patients were the time to recovery (90.32%) and safe postures (76.34%). Conclusion The majority of men and women who underwent THA reported their SF status return to baseline or have improved, mainly attributable to less pain and greater mobility. Age and severity of hip pain/stiffness were the factors that could affect patients’ SF status. Sexual education for young THA patients is needed due to the lack of related information during hospitalization.